Cheilitis Granulomatosa- Report of two cases with clinical and diagnostic implications - Amar A Sholapurkar; R Vineetha; Keerthilatha M Pai; S Suhas; Sudha S Bhat (Journal of Indian Academy of Oral Medicine and Radiology, 2006)
Cheilitis granulomatosa is a rare inflammatory disorder of unknown origin. The clinical recognition of this condition is important as is the subsequent investigation by an appropriate specialist. Management considerations for these patients needs to take into account the results of investigations, the patient′s expectations, and the severity of the condition. The multiple causes and clinical features of Cheilitis granulomatosa have created a confusing maze through which the clinician must carefully proceed in order to develop an accurate diagnosis and to provide effective treatment. The purpose of this article is to describe two cases of Cheilitis granulomatosa, highlight to the general practitioner the importance of differentiating this condition from other lip swellings.